2(v-3)-7=-3(-5v+1)-5u

Simple and best practice solution for 2(v-3)-7=-3(-5v+1)-5u equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(v-3)-7=-3(-5v+1)-5u equation:


Simplifying
2(v + -3) + -7 = -3(-5v + 1) + -5u

Reorder the terms:
2(-3 + v) + -7 = -3(-5v + 1) + -5u
(-3 * 2 + v * 2) + -7 = -3(-5v + 1) + -5u
(-6 + 2v) + -7 = -3(-5v + 1) + -5u

Reorder the terms:
-6 + -7 + 2v = -3(-5v + 1) + -5u

Combine like terms: -6 + -7 = -13
-13 + 2v = -3(-5v + 1) + -5u

Reorder the terms:
-13 + 2v = -3(1 + -5v) + -5u
-13 + 2v = (1 * -3 + -5v * -3) + -5u
-13 + 2v = (-3 + 15v) + -5u

Reorder the terms:
-13 + 2v = -3 + -5u + 15v

Solving
-13 + 2v = -3 + -5u + 15v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-15v' to each side of the equation.
-13 + 2v + -15v = -3 + -5u + 15v + -15v

Combine like terms: 2v + -15v = -13v
-13 + -13v = -3 + -5u + 15v + -15v

Combine like terms: 15v + -15v = 0
-13 + -13v = -3 + -5u + 0
-13 + -13v = -3 + -5u

Add '13' to each side of the equation.
-13 + 13 + -13v = -3 + 13 + -5u

Combine like terms: -13 + 13 = 0
0 + -13v = -3 + 13 + -5u
-13v = -3 + 13 + -5u

Combine like terms: -3 + 13 = 10
-13v = 10 + -5u

Divide each side by '-13'.
v = -0.7692307692 + 0.3846153846u

Simplifying
v = -0.7692307692 + 0.3846153846u

See similar equations:

| C/6=4 | | -4(-5w+6)-7w=5(w-5)-9 | | 2n+10=107.50 | | (-2/4)x+3=1 | | 142+2.7x=300 | | 7(n-2)-6=2n+8+n | | 900x=10 | | 2(x-.5)-6x= | | 142+2.7x=40 | | x+5-8=-2 | | -5(2w-6)+w=3(w+8) | | 3000x-6000(x+0.3)=93 | | 1=(-w+6) | | w(4-w^2)=8-w^2 | | [x-8]=11 | | 7(u+2)=42 | | 18x+4/17-17x=1/3 | | -3x-2(8+5x)=14-5(2x-5) | | 6(x+3)-10=-2(x-4) | | x+(-12)=13 | | -2(4n+4)=10 | | 3(13u-81)=21 | | x^4/y^5*y^4/x | | 78+9=4(v-9) | | |x|+1=8+15 | | 3000x=19000(x+0.7) | | 0x+1/4y=9 | | 20=14+3(y+8) | | -8x-(3x+4)=2(6x+8) | | 5a^2-20a=0 | | 17y-7=47-y | | x+(x*0.07)=118.62 |

Equations solver categories